Gateway - Pohl, Frederik (London : Gollancz, 2010)
The inhabitants of a future world find almost a thousand abandoned starships programmed for travel to distant parts of the universe, but the destination is unknown and can lead to immense wealth or death.
School Library Journal
Young Adult.
Young Adult
Keywords: Science fiction